Política hemisférica de los noventa : elementos del debate estratégico en los Estados Unidos - Morandé Lavín, José A. (Estudios Internacionales, 1996)
This paper analyzes the scope of the change in hemispheric policy in the United States in the 1990s. The replacement of the strategy of "containment" by a new one of "expansion" has meant the reaffirmation of its traditional strategic interests in the hemisphere, together with a majority adherence and commitment of the American continent to the principles of democracy and market economy. Based on the use of two broad categories (cautious-realism and optimistic-liberalism), some of the trends that are manifested in the United States are grouped and explained, and an explanation of the United States' foreign policy in the region on the basis for the interpretation of its content by North American specialists and politicians.